Pengaruh Gaya Kepemimpinan Transformasional, Hubungan Kerja Dan Tupoksi Pegawai Terhadap Kinerja Pegawai Pada Kecamatan Cibarusah Di Bekasi - Abdul Gopur; Yulianto (Reformasi Administrasi, 2025)
Transformational leadership style, harmonious working relationships, and effective implementation of duties and functions are seen as elements that play a significant role in improving employee performance. This study aims to analyze the effect of transformational leadership style, working relationships, and main tasks and functions (tupoksi) of employees on employee performance in Cibarusah District, Bekasi Regency. Employee performance is an important factor in realizing optimal public services. The research approach used is quantitative descriptive. Primary data were obtained by distributing questionnaires to 46 respondents who were employees in Cibarusah District. The data analysis technique used simple and multiple linear regression analysis to determine the effect of each independent variable on the dependent variable. The results of the study indicate that the magnitude of the influence of transformational leadership style on employee performance is 83%, work relationships are 82.90%, and the implementation of duties and functions contributes significantly to 80.60%. Simultaneously, these three variables have a significant influence on employee performance in Cibarusah District of 88.50%. This study provides recommendations to Cibarusah District to continue to improve the quality of leadership, build harmonious work relationships, and ensure that the implementation of employee duties and functions runs well in order to encourage increased performance and more optimal public services.